THE INFLUENCE OF WORK ENVIRONMENT AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT â€œSâ€ JAKARTA - Handaru, Agung Wahyu; Syafiah, Nida Hanan; Parimita, Widya (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
The purpose of this research are: 1) To know and analyze the description for the work environment, work stress, and performance of permanent employees of PT "S", 2) To know and analyze whether there is influence between the work environment on the performance of permanent employees PT "S", 3 ) To know and to analyze whether there is influence between work stress on performance of permanent employee of PT "S", 4) To know and analyze whether there is influence between work environment and work stress to performance of regular employees of PT "S". This research using descriptive and explanatory analysis. This research is taken 45 regular employees at PT "S", Jakarta. The technique of data collection used survey method by distributing questionnaires, which then processed with program SPSS 22.0. The result shows a significant influence of work environment and work stress on performance.